IMAGE FUSION DUAL ENERGY MICRO CT FOR DIFFERENTIATION OF KIDNEY STONE - ULFA JHORA (NIM: 20215013), FADHILA
Kidney stone is a disease cause by cumulation of substances in system of urinary. Knowledge about composition and type of stone is important in treatment. Micro CT is one of modality uses in determination of kidney stone composition. Some limitation are found by using single energy micro CT. Attenuation have similar value by using single energy CT, so using of dual energy micro CT is important to detect the difference of attenuation value well. Projection image of dual energy micro CT must be processing before doing analyzing. Image fusion is one of processing image method. The purpose of this research are to analyze the effect of image fusion to image quality of five number of kidney stone and to determine the composition of stone by using image fusion dual energy micro CT. The following stages in research method were collecting image projection data of both high energy and low energy, performing image fusion for both of projection data, executing reconstruction using nRecon software, and analyzing data to determine composition of stone based on attenuation value. The results were first, image fusion dual energy micro CT gave effect to image quality from its increasing of signal to noise ratio (SNR). Highest SNR gave information the best image quality. The second, image fusion dual energy micro CT could differentiate well of five number of kidney stone, but UA could not find in all five variation of image fusion.